The Influence of Digital Literacy and Digital Leadership Mediated by Employee Motivation on the Performance of East Java Province Government ASN Employees - Vebryana, Venus; Herachwati, Nuri; Nadia, Fiona Niska Dinda; Akbar, Rasyidi Faiz (GoAcademica Research & Publishing, 2024)
The increasingly rapid development of technology has led to an increase in people's needs for fast and maximum service. This causes the East Java Provincial Government through the State Civil Apparatus as public servants to be required to have good Digital Literacy and optimize digital leadership which has an impact on Work Motivation and Performance. The aim of the research is to analyze the influence of Digital Literacy and Digital Leadership on Performance through Work Motivation. Quantitative type research conducted at the East Java Provincial Government. The research population was 199 ASN of the East Java Provincial Government, using the Slovin method to determine the research sample, resulting in a total sample of 133 people. The data collection technique uses an online questionnaire via Google Form. Data analysis techniques use SEM AMOS and Sobel Test. The research results prove that Digital Literacy and Digital Leadership have a significant effect on Employee Motivation and ASN Performance. Apart from that, Employee Motivation is able to mediate the relationship between Digital Literacy and Leadership on ASN Performance